Measuring Social Capital in Indonesia: An Item Response Theory (IRT) Approach - Nurul Islamy; Rus'an Nasrudin (Universitas Udayana, 2025)
This study assesses social capital in Indonesia using the Item Response Theory (IRT) with the Graded Response Model (GRM), based on data from the 2021 Happiness Level Survey (SPTK) by Statistics Indonesia (BPS), involving 74,684 respondents. Social capital is measured across three dimensions: trust, social participation, and tolerance. Trust is further categorized into bonding (close relations), bridging (community leaders), and linking (institutions), with the highest levels in Sulawesi and the lowest in urban areas like Jakarta and Banten. Social participation is higher in rural areas, while tolerance is strongest in multicultural regions such as East Nusa Tenggara and North Kalimantan. The findings underscore the need for region-specific strategies to strengthen social capital, including institutional transparency and inclusive engagement. Reviving programs like Pendidikan Moral Pancasila (PMP) and the National Program for Community Empowerment (PNPM) can enhance trust, participation, and tolerance. The IRT-GRM model offers a robust approach for analyzing ordinal data and informing inclusive development policies.